Do Pan-African banks have the best of both worlds? - (:unkn) unknown (My University, 2018)
There has been a large expansion of foreign banks in Africa over the two decades with Pan-African banks playing a key role in this phenomenon. This paper questions if this development is beneficial for bank efficiency in African countries by investigating if Pan-African banks are more efficient than other types of foreign banks and domestic banks. We analyse the relation between ownership type and bank efficiency on a large sample of African banks covering 39 African countries over the period 2002-2015. We find that Pan-African banks are the most efficient banks in African banking industries. We explain this finding by the fact that these banks combine the best of both worlds: they have the global advantages of foreign banks and the home field advantages of domestic banks. They are then able to be more efficient than foreign banks from developed countries but also than domestic banks. This suggests that favouring entry of Pan-African banks would be beneficial to bank efficiency in Africa.
Keywords: African Research